The anaerobic degradability of thermoplastic starch: Polyvinyl alcohol blends: Potential biodegradable food packaging materials - Russo, M.A.L.; O'Sullivan, C.; Rounsefell, B.; Halley, P.J.; Truss, R.; Clarke, W.P.
A systematic study on the anaerobic degradability of a series of starch:polyvinyl alcohol (TPS:PVOH)blends was performed to determine their fate upon disposal in either anaerobic digesters or bioreactor landfills. The aims of the study were to measure the rate and extent of solubilisation of the plastics. The extent of substrate solubilisation on a COD basis reached 60
Keywords: ANAEROBIC DIGESTION; DEGRADATION; CARBOHYDRATES; STARCH; POLYVINYL ALCOHOL